Flashback of the Wayang Puppet Wali Songo Media Period and Its Relevance in Modern Life - Yosita Nadila Rahmi; Himmah Farida; Nabila Aisyiyah; Hisny Fajrussalam (Journal of Multidisciplinary Science, 2022)
Puppet as a medium of da'wah is the result of an initiative carried out by Sunan Kalijaga. Sunan Kalijaga is one of the Wali Songo members. By using wayang media, Wali Songo introduced Islam and invited people to convert to Islam voluntarily. The purpose of this study was to collect various information regarding the use of wayang as a medium of da'wah in the Walisongo era and its relevance in modern times. The method used in this research is a literature study; information is obtained and collected from several studies and existing literature. The result of the discussion is that wayang in the Wali Songo era was used as a propaganda medium to introduce Islam. However, the times have changed to modern times; the use of wayang is not only focused as a medium of da'wah but also for public entertainment.